2019
DOI: 10.1097/01.npr.0000586012.31046.c9
|View full text |Cite
|
Sign up to set email alerts
|

Increasing influenza vaccination acceptance in the homeless

Abstract: The US homeless population is predisposed to serious complications of influenza with increased likelihood of hospitalization and death. This quality improvement project sought to increase influenza vaccination in the homeless population of a rural area in the Midwest and improve provider knowledge of risks and preventive care responsibilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“… (33) A final total of 23 articles were included. [30] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… (33) A final total of 23 articles were included. [30] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] .…”
Section: Resultsmentioning
confidence: 99%
“…The sample sizes in the studies ranged from 54 (34) to 1800 people. (51) They included people who were homeless in sheltered and unsheltered settings.…”
Section: Resultsmentioning
confidence: 99%
“…The likelihood of being vaccinated was significantly higher among those with multiple primary care visits and those housed in a treatment center or nursing home affiliated with or located on the VA campus, which is likely the result of both convenient access to care and having a trusted relationship with their VA healthcare provider. Previous literature found that routine access to medical care and recommendations from a healthcare provider were strong predictors of influenza vaccination among homeless individuals [19,20] and older Veterans [47]. Additionally, healthcare workers and social service providers have been cited as the most trusted sources of information on COVID-19 vaccines among homeless Veterans [22] and HIV-positive Black Americans [48].…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine uptake among people experiencing homelessness may be hindered by various factors including vaccine hesitancy, mistrust of authorities, mental or physical impairments, lack of transportation, or competing priorities, such as finding food or shelter [17,18]. Previous research examining the general vaccine hesitancy among homeless individuals have found high refusal rates even for longstanding illnesses such as influenza [19,20] and hepatitis [21]. However, few studies have explored the COVID-19 vaccination behaviors within the general homeless population, and to date, only one has examined the vaccine attitudes of homeless Veterans [22], who comprise a significant proportion of the U.S. homeless population.…”
Section: Introductionmentioning
confidence: 99%
“…Challenges to reduce severe outcomes related to COVID-19 include access to COVID-19 vaccination [6] , [7] , [8] and a history of disproportionately low vaccine intent among PEH. [7] , [9] , [10] An understanding of vaccination intent—defined here as planning to get the COVID-19 vaccine—is important to tailor vaccine campaign strategies to maximize improvements in socio-culturally informed vaccine uptake. Available vaccines report high efficacy and safety, [11] , [12] and the U.S. population has had an overall increase in COVID-19 vaccine intent over the last year.…”
Section: Introductionmentioning
confidence: 99%